Collaborative workshop between client and agency for open innovation - Hyejeong Choi; Youngok Jeon; Hyerim Park; Ken Nah (Journal of Open Innovation: Technology, Market, and Complexity, 2018)
Innovation should be promoted by effectively managing the human factors. In the past, efforts have been made aiming to innovate by utilizing either internal or external resources. In order to innovate, there needs a circumstance where ideas can overflow as many as possible, and to look at the problem from various perspectives to find possible solutions. In this context, some discussions have arisen on how to effectively communicate and share ideas between client and agency. It is expected that collaborative workshop model can become an appropriate solution for this object. It is necessary to define a new relationship between client and agency conducive to solve design problems. To such a degree, collaborative workshop would be an effective method for achieving open innovation. This research was conducted on this key question - How the client and agency as collaborative partner can co-create innovation? How the collaborative workshop can influence the open innovation? What is the purpose of collaborative workshop? What is the process would be like? How the collaborative workshop can influence the relationship between client and agency? The research framework is as follows. Based on a literature review on the issue of collaborative workshop for open innovation, three case studies of collaborative workshop were conducted. With organizations like Crown Haiti, ISTN and Museum San among different backgrounds and workshop objectives, the results of their collaborative workshop and its processes have been compared and analyzed. In order to understand the process and its effects in collaborative workshops, a set of keywords that can describe all the behaviors and objectives in the process of three workshops are discovered. It is observed that all the keywords can be classified into several groups. This is compiled into four categories - enhancing common understanding, accelerating ideation, rapid testing, and sharing direction. The collaborative workshop model has brought forth that maps the goals and process of the collaborative workshop. It is necessary to concisely follow through each step at each category of the workshop. So the workshop includes the process of achieving each purpose.
Keywords: 650